First case report of papillary thyroid carcinoma arising within a functional teratoma in Graves' disease patient. (3rd October 2021) - Cheng, Chih-Chien; , Ting-An; Chang,; Yang, Wen-Ping
Abstract: Aim: Mature cystic teratoma is the most common kind of ovarian germ tumor. However, malignant transformation is uncommon, differentiated thyroid carcinoma is even rare. Hyperthyroidism due to coexistence of Graves' disease (GD) and struma ovarii has been reported. Functional teratoma with papillary thyroid carcinoma (PTC) in GD case has never been reported in literature. Material and method: A 48-year-old woman with GD for 4 years, who visited our hospital with complaints of severe abdominal pain for 1 day. Computed tomography of the abdominal revealed a large fat-containing lesion with dense calcification, measured 8.6 × 7.2 cm in size. Laparotomy right total oophorectomy was performed, and a huge gangrenous right ovary was noted during exploration. The final pathological diagnosis was teratoma with PTC change at right ovary. We performed thyroglobulin, TTF-1 and CK19 staining in the teratoma, the results were positive, suggesting the thyroid-hormone secretion in the PTC tissue. Result: After resection of the ovarian lesion, euthyroidism was achieved. Adjuvant thyroidectomy is not performed for no evidence of thyroid lesion or distant metastases. No GD recurrence in the 2 years after operation. The patient also does not manifest any gynecological disease symptoms, whereas the other ovary, in the follow-up ultrasound examinations, shows normal size and echo structure. Conclusion: PTC can arise within ovarian teratoma and may have thyroid hormone production. Surgeries of unilateral oophorectomy or cystectomy are a reasonable treatment, and follow-up of thyroid image and data is necessary.